The 2-hour job search : using technology to get the right job faster - Dalton, Steve, 1976- (Ten Speed Press, 2012)
"A job-search manual that gives career seekers a systematic formula to efficiently and effectively target potential employers and secure the essential first interview"--Provided by publisher.